2009
DOI: 10.1016/j.bpj.2008.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Charge Separation, Stabilization, and Protein Relaxation in Photosystem II Core Particles with Closed Reaction Center

Abstract: The fluorescence kinetics of cyanobacterial photosystem II (PSII) core particles with closed reaction centers (RCs) were studied with picosecond resolution. The data are modeled in terms of electron transfer (ET) and associated protein conformational relaxation processes, resolving four different radical pair (RP) states. The target analyses reveal the importance of protein relaxation steps in the ET chain for the functioning of PSII. We also tested previously published data on cyanobacterial PSII with open RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 68 publications
3
30
0
Order By: Relevance
“…3 were fitted to the experimental data that allowed for dissection of PSI and PSII kinetics in the fluorescence decay (32). These kinetic models for PSI and PSII are based on previous results from time-resolved measurements and fluorescence lifetime analysis of isolated PSI (44) and PSII particles (45)(46)(47)(48)(49) of vascular plants and cyanobacteria. The adequacy of these models has been discussed extensively by Holzwarth et al (32).…”
Section: Resultsmentioning
confidence: 99%
“…3 were fitted to the experimental data that allowed for dissection of PSI and PSII kinetics in the fluorescence decay (32). These kinetic models for PSI and PSII are based on previous results from time-resolved measurements and fluorescence lifetime analysis of isolated PSI (44) and PSII particles (45)(46)(47)(48)(49) of vascular plants and cyanobacteria. The adequacy of these models has been discussed extensively by Holzwarth et al (32).…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, it should be avoided at the experimental level by using carefully designed measuring conditions, such as use of proper cuvettes that allow sample refreshment, use of sufficiently low excitation intensities (see “Time-resolved fluorescence methods” and “How to achieve well-defined photosynthetic states?” sections for more details).PSII kinetics depends strongly on the measuring conditions: Charge separation in PSII with open RCs are much faster than with closed PSII RCs, resulting in substantially slower fluorescence kinetics in the closed state as compared to the open state. For example, isolated PSII cores in open and closed states have the reported average lifetimes of 65 ps and 850 ps, respectively (Miloslavina et al 2006; Szczepaniak et al 2009). Therefore, in order to be able to interpret the obtained results unambiguously, it is important to measure in a well-defined state of PSII: either at F 0 (all PSII RCs open), or F m (all PSII RCs closed) (or the corresponding F 0 ′ or F m ′ conditions).…”
Section: Time-resolved Spectroscopy On Intact Leaves: Technical Consimentioning
confidence: 99%
“…Although a limitation imposed by excited state diffusion was observed in these studies, it was concluded that this process plays a minor role in determining the effective trapping rate with respect to the kinetic bottleneck at the level of charge separation events [201, 209, 211]. On the other hand considerable evidence has also accumulated indicating that there is a partial but significant diffusion limited component in PSII, which accounts for 20-30% of the overall trapping time.…”
Section: Energy Transfer and Photochemistrymentioning
confidence: 99%